Increased GLP-1 Response after Gavage-Administration of Glucose in UCP2-deficient Mice - Zhang, H.; Li, J.; Li, Z.; Luo, Y. (Hormone and Metabolic Research, 2012)
Although it has been widely reported that endogenous level of GLP-1 can be enhanced by various secretagogues, the mechanism of GLP-1 secretion in vivo is still not fully understood. In the present study, we assessed the possible effect of uncoupling protein 2 (UCP2) on GLP-1 secretion in gut. The levels of plasma GLP-1(7–36) amide/(7–37) in UCP2-deficient mice and wild-type mice were measured by applying ELISA technique. UCP2 mRNA and protein levels were detected in the gastrointestinal tract by quantitative reverse transcription polymerase chain reaction (qRT-PCR) and Western blot analysis, respectively. The plasma GLP-1 levels in C57BL/6J mice had significantly increased to 6.9 pM (n=8, p<0.001) at 15 min after gavage-administration of glucose (2 g glucose/kg body weight), approximately 2-fold, compared with control group. Plasma GLP-1 levels were also significantly elevated at 30 min (p<0.001), but nearly returned to baseline levels at 60 min. UCP2-deficient mice had higher level of GLP-1 at various time points after administration of glucose (UCP2-deficient mice vs. wild type littermates, 15 min, 9.3±0.9 vs. 6.9±0.3, p<0.001; 30 min, 7.9±0.3 vs. 5.6±0.4, p<0.001; 60 min, 4.9±0.1 vs. 3.3±0.1, p<0.01). UCP2-deficient mice increased GLP-1 response to gavage-administration of glucose. Plasma GLP-1 level was not significantly altered after gavage-administration of saline. This study showed that plasma GLP-1 level increased after gastric glucose challenge, and UCP2 maybe serve as a negative regulator in glucose-induced GLP-1 secretion in mouse gut tract.
Keywords: UCP2; GLP-1; gut; glucose; UCP2-deficient mice